The effects of population size on agathosma collina (rutaceae) and its conservation implications - Jeffery, Douglas John (Department of Biological Sciences, 2016)
Agathosma collina is a relatively typical widespread, outcrossing shrub species, endemic to the coastal vegetation between the Agulhas Plain and Heidelberg in the Southern Cape. Although not a rare species, its endemism makes it a suitable candidate for a study of population size effects and the conservation implications for similar outbreeding species. Theory predicts that we should expect demographic problems to arise, for ecological or genetic reasons, when population size becomes too small. Initially, therefore, a study was carried out to assess if there was any discernible effect of population size on the population structure. As predicted by theory, the demographic status of small populations was worse than larger ones, measured in terms of seedling recruitment with small populations having relatively fewer seedlings than large. This effect was quite small and far from dramatic. Demographic aspects such as length of flowering, predation and seed set per capsule in different sized populations were studied. Inflorescence predation rates were found to increase to a peak during the peak flowering time of A. collina and medium sized populations showed the highest predation rate while lower predation percentages in large and small populations were probably a result of predator satiation (large populations) and crypsis (small populations). Seed set per capsule varied from mostly one seed per capsule in small and medium populations to two seeds per capsule in large populations in 1988. However, 1989 data showed an almost identical spread in the numbers of seeds per capsule in the different sized populations. None of the above results seemed sufficiently consistent over time or population size to be of importance regarding population structure differences between different sized populations. In order to obtain an indication of the amount of genetic exchange between populations, gene flow studies were carried out using pollen dispersal and seed dispersal. Although direct estimates of gene flow proved difficult to obtain, these studies indicated that gene flow was limited. Neighbourhood area resulting from estimates of pollen dispersal distances was only 2.12m² compared to ballistic seed dispersal neighbourhood area of 3.05m2, while that resulting from possible myrrnecochorous seed dispersal was 41.97m². Neighbourhood size proved to be heavily dependent on population density and was very specific to a population and care should be taken when extrapolating results to different populations or plant species. Cross pollination experiments were carried out to attempt to identify an optimal outbreeding distance. Although pollen from 7km away produced the highest capsule set of all the treatments this could have resulted from heterosis. The species is self-compatible but geitonogamous matings produced lower capsule set than outcrossed matings. Of the pollination distances which could be expected under natural circumstances the nearest neighbour crosses produced the most capsules. This corroborates the results of the gene flow studies which indicate that gene flow may be over very short distances. Inbreeding depression in small populations of A. collina seems likely since neighbourhood size is very small resulting in a low probability of pollen transfer from any great distance and since A. collina is self-compatible allowing geitonogamous matings in very small populations. Electrophoresis was then attempted to confirm the above results from a genetic aspect. Unfortunately this was not successful. This study provided some empirical support for theoretical predictions of the effects of population size on plants but suggests that the main problems may be genetic rather than ecological. The magnitude of the population size effects were small and then only in very small populations and are therefore probably only of concern under rare circumstances. Bibliography: pages 100-111.